EXPECTATION FACTORS OF SOCIAL MEDIA INFLUENCING CHINESE FANCLUB WITH THAI SUPERSTAR, EASTERN CHINA: Received: 28th February 2022; Revised: 16th May 2022, 26th May 2022; Accepted: 27th May 2022 - Zhang, Yidi; Sutunyarak, Chonlavit (PEOPLE: International Journal of Social Sciences, 2022)
With the widespread of Thai dramas on Chinese social media, Thai drama fans in eastern China’s growing and set up many Fanclub, the Thai star in the Chinese fans harvest high likability. This study adopted the fan economic theory proposed by Zhang (2010), set the sample as fans who like Thai superstars in East China, and used a questionnaire to survey 432 people. The results of the study show that 99.54% of respondents in East China have a favorite Thai superstar and there are 395 female fans, indicating that female fans are more satisfied with Thai superstars, and the high satisfaction of fans with Thai superstars has a greater impact on their tourism consumption in Thailand. Through the analysis of this research, it has become a guide to help Thailand increase tourism revenue and help Thailand develop new products for Chinese movie fans. Thailand can combine tourism and idol elements to create idol-themed tourism routes and launch daily products aimed at Chinese fans. The sample size of male fan groups in this study is small, and follow-up research can strengthen the research on male fan groups.